\[\boxed{\text{672\ (672).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ \left( y^{2} \right)^{3} = y^{6}\]
\[2)\ \left( 2x^{3} \right)^{3} = 8x^{9}\]
\[3)\ \left( 3a^{2}b^{4} \right)^{3} = 27a^{6}b^{12}\]
\[4)\ \left( 0,1mn^{5} \right)^{3} = 0,001m^{3}n^{15}\]
\[5)\ \left( \frac{1}{6}b^{6}c^{7} \right)³ = \frac{1}{216}b^{18}c^{21}\]
\[6)\ \left( \frac{2}{7}p^{10}k^{15} \right)^{3} = \frac{8}{343}p^{30}k^{45}\]
\[\boxed{\text{672.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ (7n + 4)^{2} - 9 =\]
\[= (7n + 4 - 3)(7n + 4 + 3) =\]
\[= (7n + 1)(7n + 7) =\]
\[= 7 \cdot (7n + 1)(n + 1) \Longrightarrow\]
\[\Longrightarrow делится\ на\ 7.\]
\[2)\ (8n + 1)^{2} - (3n - 1)^{2} =\]
\[= (5n + 2) \cdot 11 \cdot n \Longrightarrow делится\ \]
\[на\ 11.\]
\[3)\ (3n + 7)^{2} - (3n - 5)^{2} =\]
\[= 12 \cdot (6n + 2) =\]
\[= 12 \cdot 2 \cdot (3n + 1) =\]
\[= 24 \cdot (3n + 1) \Longrightarrow делится\ на\ \]
\[24.\]
\[4)\ (7n + 6)^{2} - (2n - 9)^{2} =\]
\[= (5n + 15)(9n - 3) =\]
\[= 5 \cdot (n + 3) \cdot 3 \cdot (3n - 1) =\]
\[= 15 \cdot (n + 3)(3n - 1) \Longrightarrow\]
\[\Longrightarrow делится\ на\ 15.\]